EPIDEMIOLOGICAL ANALYSIS OF TRENDS IN DHF CASES IN MALANG CITY - Swaidatul Masluhiya AF; Irma Irma (Universitas Muhammadiyah Magelang, 2021)
Dengue Hemorrhagic Fever (DHF) is a disease caused by a virus which is still a public health problem whose number of sufferers is getting higher and its area of distribution is expanding which can cause death. DHF is also still endemic and continues to spread throughout the city of Malang. This research is descriptive qualitative research that aims to see the tendency of DHF cases in Malang City based on the variables of person, place and time of occurrence. The population and samples used were all data on DHF patients in Malang City which were obtained from the Malang City Health Office for the period 2015 - 2020 as many as 1.717 cases. The results of the data analysis of this study indicate that cases of DHF in Malang City always experience an increase from January to June with the highest peak in May every year, mostly 34.8% of DHF cases occur in Lowokwaru District and the majority (54.62%) are women and most (51.81%) are in the age group 15-44 years. There is a need for maximum prevention and control of dengue fever, especially before the increase in cases at the beginning of the year, especially in the Lowokwaru District which is the work area of the Dinoyo Public Health Center, Kendalsari and Mojolangu.